2012
DOI: 10.1038/ng.1068
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic repression of cardiac progenitor gene expression by Ezh2 is required for postnatal cardiac homeostasis

Abstract: Adult-onset diseases can be associated with in utero events, but mechanisms for this remain unknown1,2. The polycomb histone methyltransferase, Ezh2, stabilizes transcription by depositing repressive marks during development that persist into adulthood3–9, but its function in postnatal organ homeostasis is unknown. We show that Ezh2 stabilizes cardiac gene expression and prevents cardiac pathology by repressing the homeodomain transcription factor Six1, which functions in cardiac progenitors but is stably sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
235
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(246 citation statements)
references
References 26 publications
9
235
1
1
Order By: Relevance
“…S3). For Tnni2 and Myl1, we focused the ChIP on previously identified responsive elements (19)(20)(21). DNA from adult-heart-derived chromatin, following Prox1 immunoprecipitation, was enriched for Tnnt3, Tnni2, and Myl1, with binding specificity confirmed using chromatin from age-matched Prox1 mutant hearts ( Fig.…”
Section: Resultsmentioning
confidence: 85%
“…S3). For Tnni2 and Myl1, we focused the ChIP on previously identified responsive elements (19)(20)(21). DNA from adult-heart-derived chromatin, following Prox1 immunoprecipitation, was enriched for Tnnt3, Tnni2, and Myl1, with binding specificity confirmed using chromatin from age-matched Prox1 mutant hearts ( Fig.…”
Section: Resultsmentioning
confidence: 85%
“…In contrast, conditional deletion of Ezh2 in anterior heart field progentitor cells did not disrupt cardiac specification and development but rather induced cardiomyocyte hypertrophy. Interestingly, these effects appear to be dependent on Six1, a cardiac progenitor cell TF that is developmentally shut down in differentiated myocytes [81].…”
Section: Histone Methyltrasnferases Are Required For Cardiomyocyte Prmentioning
confidence: 99%
“…Six1 is normally repressed by Ezh2, which functions to stabilize cardiac gene expression upon differentiation and to maintain postnatal cardiac homeostasis [81,82]. However, deletion of Ezh2 in differentiated cardiomyocytes does not cause any overt phenotype, which could be due to functional redundancy with Ezh1 at later stages of development [79].…”
Section: Histone Methyltrasnferases Are Required For Cardiomyocyte Prmentioning
confidence: 99%
“…Among the PRC2 components, loss of Suz12, Ezh2, or Eed results in embryonic lethality during the early postimplantation stage [12][13][14]. To address the role of PRC2 in cardiac development, Ezh2 and Eed were conditionally inactivated in specified cardiac cells using Nkx2-5:Cre or TnT:Cre [3,4]. Inactivation of Ezh2 by Nkx2-5:Cre (Ezh2 NK ) and Eed by TnT:Cre (Eed TnT ) led to embryonic lethality and several cardiac defects including compact myocardial hypoplasia, whereas inactivation of Ezh2 by TnT:Cre (Ezh2 TnT ) did not result in severe defects in cardiogenesis despite a modest upregulation of some cardiac genes, probably because of the redundant functions of Ezh1 and Ezh2.…”
Section: Pcg Functions In Cardiac Developmentmentioning
confidence: 99%
“…Traditionally, focus on causes of CHD has involved transcriptional networks during cardiogenesis, because correct alignment and septation of cardiac structures regulated by cardiac specific transcriptional factors, such as Tbx1, Tbx5, Tbx20, Gata4, and Nkx2-5, are essential for cardiac morphogenesis [1]. In addition to these multiple genetic factors, recent studies have shown that some chromatin remodeling factors moderate gene expression to control cardiogenesis and are also involved in the molecular pathogenesis of CHD [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%